Population Bulge and Food Security in Nigeria: A Positive or Negative Nexus - SULE, Babayo (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose - Nigeria is the seventh most populous country in the world, and estimated population growth suggests that it will become the fourth most populous country by 2050. Population distribution shows a dominant youth bulge and geometric growth in the last three decades. However, blessed with a large population, Nigeria suffers from hunger and food insecurity, with an estimated 23 million (10.55%) facing food shortages in 2023. Therefore, the question arises whether there is a link between population explosion and food security in Nigeria. Methodology - This study answers the puzzle of the relationship between population growth and food security in Nigeria. The study uses documented sources and empirical data and applies content analysis to discuss the significant findings. Findings - The study concludes that the population explosion is not a curse or negative phenomenon causing food insecurity in Nigeria. However, relatively ineffective agricultural policies, conflicts in agricultural areas, displacement through insurgency, banditry and conflicts between farmers and herders, climatic factors, and underutilized youth and land are more responsible for the food security crisis than population growth. Implication - Therefore, the study recommends, among other things, that agricultural policies must be changed to a modern farming system and that youth must be involved in profitable agricultural production to increase productivity and ensure food security in the future.